Free time [videorecording (DVD)] - Brown, Ryan Martin; Burgess, Colin; Suresh, Rajat; Zuckerman, Justin (Greenwich Entertainment, 2025)
Drew is approaching the end of his twenties and, with it, his relative youth. Looking to make a sudden change, he decides to quit his cushy desk job and 'embrace life.' Cycling quickly through friends, hobbies, and goals, it's not long until Drew realizes he has no idea what to do with his newfound freedom.